Identifying the zero-dose and under-immunized children in Bangladesh: Approaches and experiences. - Zerin Jannat; Hemel Das; Md Wazed Ali; Nurul Alam; Mahbub E Elahi Khan Chowdhury; Bidhan Krishna Sarker; Md Mahbubur Rahman; Shehrin Shaila Mahmood; Md Musfikur Rahman; Christopher Morgan; Elizabeth Oliveras; Gustavo Caetano Correa; et al. (PLoS ONE)
This paper presents and elaborates on empirical methods and approaches used to identify Zero-Dose (ZD) and Under-immunized (UI) children as well as the communities that these children reside in within Bangladesh. This paper also describes demand- and supply side-barriers that lead to children being ZD and UI in the country. Time period for the study was December 2022-May 2023. The study methodology encompassed secondary data analysis using data from national surveys, primary data collection and analysis via a lot quality assurance sampling (LQAS) survey and also, qualitative data collection and analysis. Study population included caregivers of children aged 4.5 months (4 months 15 days) to 23 months for the LQAS survey. The qualitative component included policymakers, program managers and service providers working in immunization as well as mothers in the selected study areas who had a living child aged less than 2 years as the study population. Our data analysis confirms existence of ZD and UI children in areas which were categorized into haor (wetlands), hilly, char (sandy/silty land surrounded by water), coastal, plain land and urban slums. Determinant analysis showed that the mother's level of education, antenatal visits made, and access to media were significantly associated with children being ZD or UI. Reproductive autonomy emerged as a key factor that had prominent impact on a child being ZD. The qualitative analysis indicated the importance of population migration, health workforce shortages and lack of access to transportation as prominent barriers to immunization. Notably, the methods and approaches used in this study are both effective and easily replicable to identify ZD and UI children. The drivers of ZD and UI along with the barriers to immunization provide potential areas for intervention by policy-makers and can apprise about interventions to be tested in future implementation research.